Processable and printable acrylic films and articles formed therefrom

JP2025506749AActive Publication Date: 2025-03-13AVERY DENNISON CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024549481
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-22
Filing Date
2023-02-22
Publication Date
2025-03-13
Estimated Expiration
2043-02-22

Smart Images

  • Figure 2025506749000009
    Figure 2025506749000009
  • Figure 2025506749000010
    Figure 2025506749000010
  • Figure 2025506749000011
    Figure 2025506749000011
Patent Text Reader

Abstract

(Summary of disclosure) Flexible acrylic polymer and thermoplastic elastomer combination films are disclosed that are compatible, processable, and printable like thermoplastic PVC, as well as articles comprising these films with adhesive and optional printed indicia and optional liners.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims priority to U.S. Provisional Application No. 63 / 312,550, filed February 22, 2022, which is incorporated herein by reference in its entirety.

[0002] FIELD OF THEINVENTION The present invention relates generally to polymeric films. More specifically, the present invention relates to films comprising polymer blends that are processable and printable and useful for graphic and related applications. [Background technology]

[0003] BACKGROUND OF THEINVENTION Graphic articles are used for many different purposes to provide information for advertising and decoration. Graphic articles may include a single layer film or multiple layers of film and an adhesive layer to adhere the graphic film to a substrate. Graphic articles need to be flexible to allow for their attachment to a wide range of surfaces and objects. Some or all of the layers of the film may contain images, such as printed images, to create a graphic pattern or design. In addition, some other properties that are desirable in graphic articles include good tear resistance and weatherability.

[0004] Thermoplastic polyvinyl chloride (PVC) films have been widely used for both indoor and outdoor graphic applications such as promotional or advertising campaigns, although other polymeric films are also useful. Such applications include signs, banners, fleet graphics, vehicle wraps, architectural and wall coverings, consumer product labeling, and other pressure-sensitive products. They are often used in applications that require processability, conformability, and printability. Unfortunately, PVC-based formulations often result in fogging due to the release of hydrogen chloride (HCl) upon combustion. The released HCl fumes and their decomposition pose health hazards. Furthermore, to achieve the soft and conformable properties of flexible polyvinyl chloride, the current practice is to compound PVC with phthalates, which carry health risks. Furthermore, PVC production typically requires vinyl chloride starting material, which is undesirable. Vinyl chloride production as well as the incineration of waste PVC (or waste PVC) create harmful dioxins. Therefore, there is a need for a film composition that has the characteristics of PVC-based formulations, but lacks PVC and its inherent disadvantages.

[0005] Various acrylics have been proposed as replacements for PVC. However, many of the acrylic films are too rigid for certain end uses or possess poor tear resistance. The multi-stage acrylic polymers taught in U.S. Pat. No. 1,004,0915 possess high moduli, making them challenging to process for certain applications. Some commercial acrylics, including block polymers, are flexible but exhibit poor tear resistance. Furthermore, none of these films are inherently printable, requiring a separate print-receptive layer or treatments such as corona treatments to adequately accept and retain printing ink.

[0006] Polyurethane-based films have also been proposed to replace PVC. These films are desirable for graphic applications due to their properties such as abrasion resistance, mechanical strength, and weatherability. Polyurethane film sheets can be efficiently prepared by the calendaring method. However, the processing temperature range of polyurethane is very small, which leads to difficulties in continuous production, including low production speeds. Furthermore, polyurethane-based films are very expensive for end use. Moreover, some of these films, particularly TPU films with a Shore D hardness of more than 65, lack the flexibility required for graphic applications.

[0007] There are alternative polymeric films proposed to replace PVC films. For example, JP2004039643 discloses a calenderable film comprising 100 parts by weight of thermoplastic polyurethane, 1-40 parts by weight of calcium carbonate having an average particle size of 0.3-1.5 μm, and 0.1-1.5 parts by weight of an organic acid metal salt. The patent discloses that the thermoplastic polyurethane can be blended with an acrylic soft resin, the thermoplastic polyurethane being present at a level of 50-95% by weight, and the acrylic soft resin being present at a level of 5-50% by weight. The patent discloses that it is necessary to use calcium carbonate of a specified average particle size range to prevent blocking and allow easier handling. Furthermore, the patent discloses that it is necessary to incorporate an organic acid metal salt in a specified average particle size range together with calcium carbonate, and that without this incorporation there is insufficient improvement in the calendering properties of the polymer composition. However, films containing these additives are lacking in terms of printability.

[0008] Current offerings do not appear to address the need for a film that has the compatibility, processability, and printability of PVC without the inclusion of PVC. The films of the present invention are directed to these, as well as other important objectives. Summary of the Invention [Means for solving the problem]

[0009] (Summary of the invention) The present invention relates generally to a film that is compatible and processable, particularly calenderable, yet printable, as required for end use applications. Thus, the film of the present invention provides an alternative to PVC.

[0010] Thus, one aspect of the invention is directed to a film comprising a polymer blend, the polymer blend comprising 50% to 100% by weight of a flexible acrylic resin, based on the total weight of the blend; 0% to 50% by weight of a thermoplastic urethane elastomer, based on the total weight of the blend; 0.1% to 10% by weight of a high molecular weight organic lubricant, based on the total weight of the blend; and an optional pigment, the film being both processable and printable. In some embodiments, the film comprises 1% or less by weight of a filler, based on the total weight of the blend.

[0011] In another aspect, the invention is directed to an article comprising a film as described herein, the film having a first side and a second side; an adhesive layer applied to at least a portion of the first side of the film; and an optional printed indicia applied to at least a portion of the second side of the film.

[0012] The Summary of the Invention is provided as a general introduction to some embodiments of the invention and is not intended to be limiting. Further exemplary embodiments, including modifications and alternative configurations of the invention, are provided herein.

[0013] BRIEF DESCRIPTION OF THE DRAWINGS The patent or application file contains at least one color drawing. Copies of this patent or patent application publication containing color drawing(s) will be provided by the Office upon request and payment of the necessary fee.

[0014] The accompanying drawings are included to provide a further understanding of the invention, are incorporated in and constitute a part of this specification, illustrate embodiments of the invention and, together with the description, serve to explain the principles of the invention. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 shows an exemplary embodiment of an article comprising a representative film of an embodiment of the present invention, a pressure sensitive adhesive, optional printed indicia, and an optional release liner. [Diagram 2] FIG. 2 shows a black and white representation of a representative test chart for film media when printed on HP Latex Gen III used in the Chroma Test (or Chroma Test) of the examples. [Diagram 3] FIG. 3 shows a black and white representation of a representative sample book (or swatch book) used in the chroma testing of the examples. [Figure 4] FIG. 4 shows a black and white representation of a representative two-dimensional chart of C values ​​(area or area) used in the chroma testing of the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] DETAILED DESCRIPTION OF EXEMPLARY EMBODIMENTS definition As used above and throughout this disclosure, the following terms, unless otherwise indicated, shall be understood to have the following meanings:

[0017] As used herein, the terms "comprises," "comprising," "includes," "including," "has," "having," or any other variation thereof, are intended to be open ended and cover a non-exclusive inclusion. For example, a process, method, article, or apparatus that includes a list of elements is not necessarily limited to only those elements and may include other elements not expressly listed or inherent to such process, method, article, or apparatus. Also, the use of "a" or "an" is employed to describe elements and components described herein. This is done merely for convenience and to give a general sense of the scope of the invention. This description should be read to include "one" or "at least one," unless the context clearly indicates otherwise, and the singular includes the plural. As used herein, the term "about" when referring to a measurable value, such as an amount, time over time, etc., is meant to encompass variations of ±10%, preferably ±8%, more preferably ±5%, even more preferably ±1%, and even more preferably ±0.1% from the specified value, where such variations are appropriate.

[0018] As used herein, "pressure sensitive adhesive" or "PSA" refers to a material that can be identified by the Dahlquist scale, which is a pressure sensitive adhesive that is identifiable by a viscosity modulus of 1×10 as described in Handbook of PSA Technology, Donatas Satas (Ed.), 2nd Edition, p. 172, Van Nostrand Reinhold, New York, NY, 1989. -6 cm 2 We define a pressure sensitive adhesive as an adhesive that has a 1 sec creep compliance of greater than 1×10 / dyne. Since the elastic modulus (or modulus or modulus) is, to a first approximation, the reciprocal of the creep compliance, a pressure sensitive adhesive has a creep compliance of greater than 1×10 6 dyne / cm 2Another well-known means of identifying a pressure-sensitive adhesive is as described in the 1996 Glossary of Terms Used in the Pressure Sensitive Tape Industry by the Pressure Sensitive Tape Council as an adhesive that is aggressively and permanently tacky at room temperature without the need for more than finger or hand pressure, adheres firmly to a variety of dissimilar surfaces upon mere contact, and can be removed from smooth surfaces without leaving a residue. Another suitable definition of a suitable pressure-sensitive adhesive is preferably one that has the following points plotted on a graph of elastic modulus versus frequency at 25° C.: at a frequency of about 0.1 radians / second (0.017 Hz), approximately 2×10 5 ~4×10 5 dyne / cm 2 and a frequency of about 100 rad / s (17 Hz), 6 ~8×10 6 dyne / cm 2 and having a room temperature storage modulus within a region defined by the modulus range of 1000 .mu.m. See, e.g., Handbook of PSA Technology, 2nd Edition, p. 173, Donatas and Satas, eds., Van Nostrand Rheinhold, NY, 1989. Any of these methods of characterizing pressure sensitive adhesives may be used to identify pressure sensitive adhesives suitable for use in the film structures of the present invention.

[0019] As used herein, the "glass transition temperature" or "T g " refers to the glass transition temperature calculated by the following Fox equation [Bulletin of the American Physical Society 1, 3 Page 123 (1956)] (wherein copolymers contain two monomers):

[0020] [Number 1] 1 / T g =w1 / T g1 +w2 / Tg2

[0021] For copolymers, w1 and w2 refer to the weight fraction of the two comonomers relative to the weight of the monomers charged to the reaction vessel, and T g1 and T g2 refers to the glass transition temperatures of the two corresponding homopolymers in degrees Kelvin. For polymers containing three or more monomers, additional terms are added (w n / T g(n) For purposes of this invention, the glass transition temperatures of homopolymers are those reported in "Polymer Handbook," edited by J. Brandrup and E.H. Immergut, Interscience Publishers, 1966, unless that publication specifically discloses the T g Unless the T is reported, the homopolymer T g is measured by differential scanning calorimetry (DSC) at a heating rate of 10°K / min.

[0022] As used herein, the term "film" refers to an object having one dimension (thickness) that is relatively small compared to the other two dimensions (length and width). The thickness of a film is between 0.01 mm and 2 mm. The length and width of a film are each 1 cm or greater. The surfaces of a film defined by the length and width of the film are known herein as the "faces" (or first and second sides) of the film.

[0023] As used herein, the term "adhesive layer" refers to a layer or layers of the same or different pressure sensitive adhesive that is applied to at least a portion of a first side of the film of the present invention.

[0024] As used herein, the term "release liner" refers to a film sheet (typically paper or polymeric film, usually applied during the manufacturing process) used to prevent premature adhesion of sticky surfaces. Release liners are coated on one or both sides with a release agent to provide a release effect for any type of sticky material, such as an adhesive or mastic.

[0025] As used herein, "printed indicia" means any series of alphanumeric or special characters used to convey information (e.g., name, residential or mailing address, telephone number, prescription number) and / or to provide aesthetic appeal. The indicia may be printed by any suitable means, including handwritten, typewritten, or conventional printing (e.g., flexographic, offset, inkjet, laser inkjet, videojet, thermal transfer, direct printing, gravure, digital printing, etc.).

[0026] The term "flexible acrylic resin" or "FAR" as used herein refers to a (meth)acrylic polymer (preferably all (meth)acrylic polymers) that has a flexibility similar to plasticized PVC at room temperature, i.e., a modulus of elasticity of 0.001 GPa to 1.8 GPa, as measured by ASTM D882-18 (at a speed of 5 in / min). FAR contains polymerized residues of at least two types of (meth)acrylate monomers, where one has a high glass transition temperature (preferably greater than 25°C as measured by differential scanning calorimetry according to ASTM-D3418-21) and one has a low glass transition temperature (preferably less than 20°C as measured by differential scanning calorimetry according to ASTM-D3418-21). FAR may contain small amounts of other monomers, particularly (meth)acrylate monomers such as (meth)acrylic acid. FAR may be in various polymeric structures and morphologies, such as block copolymers, core-shell or multi-layered polymer particles. For example, the FARs can be core-shell or multi-layered acrylic polymer particles prepared by a sequential emulsion polymerization process, such as those processes described in U.S. Pat. No. 10,040,915 and WO 2020 / 197797, the entire disclosures of which are incorporated herein by reference.

[0027] As used herein, the prefix "(meth)acryl-" refers to both "methacryl-" and "acryl-", such as "(meth)acryl" (meaning both methacrylic and acrylic), "(meth)acrylate" (meaning both methacrylate and acrylate), and "(meth)acrylonitrile" (meaning both methacrylonitrile and acrylonitrile). The term "(meth)acrylate" refers to an acrylic or methacrylic acid ester of a monomeric alcohol. Acrylate and methacrylate monomers are collectively referred to herein as "(meth)acrylate" monomers. Polymers prepared from (meth)acrylate monomers are referred to as (meth)acrylate polymers.

[0028] As used herein, the term "acrylic polymer" refers to at least one (meth)acrylate homopolymer or copolymer, and can include blends of different (meth)acrylate polymers and copolymers.

[0029] The term "polymer" as used herein will be understood to include polymers, copolymers (eg, polymers formed with two or more different monomers), oligomers, and combinations thereof.

[0030] As used herein, the term "copolymer" refers to a polymer that contains copolymerized units of at least two different monomers.

[0031] As used herein, the term "ethylenically unsaturated," when used to describe a monomer or group, refers to a monomer or group that contains a terminal ethylene group (H2C=CH-).

[0032] As used herein, "gsm" means grams per square meter.

[0033] As used herein, "Shore hardness" is a standardized measurement of the hardness of a material measured using a durometer having a dimensionless output on a scale of 0 to 100 (higher readings indicate harder materials) in accordance with ASTM D2240-15 (2021) and ISO 868:2003 (2018). A measurement of 80 on the Shore Hardness A scale corresponds to a measurement of 29 on the Shore Hardness D scale.

[0034] As used herein, "conformable" means a film that can substantially conform to the underlying surface to which it is applied, such that the exposed surface of the conformable film mimics the topology of the underlying surface.

[0035] As used herein, "metal detachment" is an assessment of processability. To assess metal detachment, a material or blend of materials is heated under pressure in a metal two-roll mill at the conditions given in the Examples. After complete melting (or fusion) of the material, the gap is set to the lowest value the film is capable of, which is typically about 50 mμ, but can vary depending on the rheology of the material. The speed for sampling is reduced to one that allows manual peeling (e.g., 20 rpm for the cylinder). Manual peeling of the film from the metal surface of the roll is: Ease of peeling (manual force required to peel) and location of the peel line; and 3=Good / Acceptable, 2=OK (or OK) / Acceptable, and 1=Bad / Unacceptable It is subjectively determined based on

[0036] As used herein, "printability" refers to the ability of a film to be printed with ink to form a printed indicia that meets the requirement of a chroma area (or chroma area, chroma area, saturation area or chroma area) of at least 99 as measured by the Chroma Area rating described in the Examples.

[0037] As used herein, "roll blocking" refers to a film or film structure defect that occurs when adjacent films or film structures fuse or adhere together and that can be observed when the film or film structure is unwound from a roll. Blocking can be evaluated using the T-Peel test (units: N / inch) as described in the Examples, with ratings of <1.25=acceptable (roll blocking is prevented), >1.25=poor / unacceptable (roll blocking is not prevented).

[0038] All percentages stated herein are by weight, based on the weight of the composition, unless otherwise specified.

[0039] The present invention relates generally to films, particularly to processable and calenderable thin films. The film provides an alternative to PVC and provides desirable properties for graphic articles, including, for example, tear resistance and weatherability. In some embodiments, the film has at least the same compatibility as PVC, substantially the same compatibility as PVC, or PVC-like compatibility. Advantageously, the film does not suffer from the health risks associated with PVC films; the poor compatibility, tear resistance, printability of traditional acrylic films; and the lack of compatibility of polyurethane films. Thus, the film is suitable for a variety of end uses. The present invention will be described in more detail with respect to the film and the article comprising the film.

[0040] The film is processable, for example, via melt processes such as extrusion, blowing, and especially calendering. The calenderability of the film can be measured by the ease with which the film can be stripped of metal. Methods for evaluating metal stripping are described above. Alternatively, calenderability can be evaluated by the ease with which the film can be unwound from a roll without defects or without substantial defects (also known as prevention of roll blocking), especially without a carrier. In addition to being processable, the film is also printable.

[0041] In some embodiments, the film has a thickness of 0.01 mm to 2 mm, 30 μm to 200 μm, 50 μm to 150 μm, or 80 μm to 120 μm.

[0042] Accordingly, some embodiments of the present invention are directed to a film comprising a polymer blend comprising 50% to 100% by weight of a flexible acrylic resin, based on the total weight of the blend; 0% to 50% by weight of a thermoplastic urethane elastomer, based on the total weight of the blend; 0.1% to 10% by weight of a high molecular weight organic lubricant, based on the total weight of the blend, and optionally a pigment. As previously described herein, the film is both processable and printable. The film is characterized by a viscosity in the range of 1,000 Pa.s to 150,000 Pa.s at 170° C. and 10 rad / s.

[0043] In certain embodiments, the flexible acrylic resin is present at a level of 50% to 100% by weight, or 50% to 95% by weight, based on the total weight of the blend. All individual values ​​and subranges are disclosed and included herein; for example, the amount of flexible acrylic resin can be from a lower limit of 50, 55, 60, 65, or 70 weight percent to an upper limit of 75, 80, 85, 90, or 95 weight percent. For example, the amount of flexible acrylic resin can be in the range of 50 to 95% by weight, or alternatively 60 to 90% by weight, or 65 to 85% by weight, or 70 to 80% by weight, or 50 to 60% by weight, or 50 to 70% by weight.

[0044] In some embodiments, the flexible acrylic has a Shore D hardness of about 40 to about 60, about 45 to about 55, or about 50 to about 60. "Shore D hardness" refers to a standardized test that involves measuring the depth of penetration of a specific indenter. The hardness value is determined by the penetration of the foot of a durometer indenter into a sample.

[0045] Any suitable flexible acrylic resin can be used. In some embodiments, the flexible acrylic resin is a block polymer. In some embodiments, the flexible acrylic resin is a multi-stage polymer. In some embodiments, the flexible acrylic resin is a block copolymer, a multi-stage polymer, or both. In some embodiments, the flexible acrylic resin is a block copolymer prepared from poly(methyl methacrylate) (PMMA) and butyl acrylate (BA). In certain embodiments, the flexible acrylic resin is an ABA type block copolymer. In some embodiments, the ABA type block copolymer is prepared from poly(methyl methacrylate) (PMMA) and butyl acrylate (BA). In some embodiments, the flexible acrylic resin comprises a multi-stage acrylic polymer. In some embodiments, the multi-stage acrylic polymer is a low T g In some embodiments, the low T g The monomer is selected from butyl acrylate, 2-ethylhexyl acrylate, or both. In some other embodiments, the flexible acrylic resin does not include a hydrogen-bonding monomer.

[0046] In some embodiments, the polymer blend includes a urethane polymer that is thermoplastic. Thermoplastic urethane elastomers (also known as thermoplastic polyurethanes, thermoplastic urethane polymers, TPUs) are the reaction product of polyisocyanates with polyols and, optionally, polyamines.

[0047] A polyisocyanate is a compound having two or more isocyanate groups per molecule. Any suitable polyisocyanate can be used, such as aromatic diisocyanates, aromatic-aliphatic diisocyanates, cycloaliphatic diisocyanates, polymeric or oligomeric compounds (e.g., polyoxyalkylenes, polyesters, polybutadienes, etc., terminated with two or more isocyanate functional groups), and combinations thereof. A suitable polyol is a molecule having two or more hydroxyl groups per molecule. Suitable polyols include, for example, polyether polyols, polyester polyols, polycarbonate-based polyols, polyethylene glycols, and mixtures thereof. A polyamine or polyamines is a compound having two or more amine groups per molecule. When present, the polyamine or polyamines can be an aliphatic polyamine, an aromatic polyamine, or mixtures thereof.

[0048] A suitable TPU can be any type of TPU. For example, a suitable TPU can be an aliphatic TPU, an aromatic TPU, or a TPU that includes at least one aliphatic component and at least one aromatic component. In some embodiments, one or more TPUs of the present invention are aliphatic. In an aliphatic TPU, each of the polyisocyanate, polyol, and polyamine (if used) is aliphatic. As used herein, "aliphatic" means linear aliphatic, branched aliphatic, cyclic aliphatic, or mixtures thereof. In some embodiments, one or more TPUs of the present invention are aromatic. An aromatic component is a component that includes one or more aromatic rings. In an aromatic TPU, at least one of the polyisocyanate, polyol, and polyamine (if used) is aromatic. As used herein, "aromatic" includes linear aromatic, branched aromatic, or mixtures thereof.

[0049] In some embodiments, the polymer blend comprises a polyether-based thermoplastic polyurethane. In some embodiments, the polymer blend comprises a polyester-based thermoplastic polyurethane. In some embodiments, the polymer blend comprises a polycarbonate-based thermoplastic polyurethane. In some embodiments, the polymer blend comprises at least one of a polyether-based polyurethane, a polyester-based polyurethane, or a polycarbonate-based polyurethane. The thermoplastic urethane elastomer, if present, has a Shore D hardness of about 55 to about 95, about 60 to about 90, or about 65 to about 85, or about 70 to about 80, or about 60 to about 70. In some embodiments, the thermoplastic urethane elastomer has a Shore D hardness of at least 65.

[0050] In certain embodiments, the thermoplastic urethane elastomer is present at a level of 0% to 50% by weight, based on the total weight of the blend, or at a level of 5% to 50% by weight, based on the total weight of the blend. All individual values ​​and subranges are disclosed and included herein; for example, the amount of thermoplastic urethane elastomer can be from a lower limit of 0, 1, 5, 10, 15, 20, 25, 30, or 35 weight percent to an upper limit of 25, 30, 35, 40, 45, or 50 weight percent. For example, the amount of thermoplastic urethane elastomer can range from 0 to 50% by weight, or alternatively, from 5 to 50% by weight, or 10 to 40% by weight, or 20 to 30% by weight, or 30 to 50% by weight, or 40 to 50% by weight.

[0051] The polymer blend further comprises a high molecular weight organic lubricant. It has been unexpectedly found that the high molecular weight organic lubricant improves the processability of the polymer blend, especially in calendering. In certain embodiments, the high molecular weight organic lubricant is a high molecular weight polyester lubricant. "High molecular weight" as used herein means having a molecular weight of at least 1,500 Da. In some embodiments of the present invention, the molecular weight of the lubricant ranges from 1,500 Da to 50,000 Da. The polymer polyester is a reaction product of a fatty acid and an alcohol. In certain embodiments, the polymer polyester is a reaction product of a fatty acid selected from oleic acid, stearic acid, hydroxystearic acid, or any combination thereof; and an alcohol selected from butanol, octanol, glycerol, pentaerythritol, or any combination thereof. In some embodiments, the high molecular weight polyester is a reaction product of oleic acid and n-octanol. In some embodiments, the high molecular weight polyester is a reaction product of stearic acid and n-butanol. In some embodiments, the high molecular weight polyester is a reaction product of a fatty acid and glycerol. Surface migration of lubricants reduces the quality of polymer composites, especially affecting printing performance. The high molecular weight organic lubricants included in the present invention exhibit lower migration toward the surface of films prepared from the polymer blends.

[0052] In some embodiments, the high molecular weight organic lubricant is present in an amount ranging from 1% to 10%, 1% to 5%, 2% to 4%, or 3% to 4% by weight based on the total weight of the blend. Polymer blends containing lubricants outside the claimed ranges may render the film unworkable or adversely affect the print quality of the film.

[0053] In certain embodiments, the polymer blend further comprises a pigment. Pigments are organic or inorganic compounds that are added to the polymer base to impart a particular color or functional advantage. In some embodiments, the pigment is at least one compound selected from the group consisting of phthalocyanine blue, ultramarine, barium sulfate-permaganate, carbon black, antimony titanate, cobalt titanate, iron oxide, titanium dioxide, benzimidazolone, perylene, pyrathrone, pyrazoquinazo, quinacridone, quinophthalone, zirconium vanadium, nickel niobium titanium, and isoindoline. In a preferred embodiment, the pigment is a white pigment, such as titanium dioxide.

[0054] In some embodiments, the film comprises 1 wt.% or less of a filler, based on the total weight of the blend. By "filler" herein is meant an organic or inorganic compound, such as, for example, calcium carbonate, that is introduced into a polymeric composite or blend to change or modify the properties of the polymeric composite or blend. In some embodiments, the film comprises less than 0.75 wt.% of a filler, based on the total weight of the film. In some embodiments, the film comprises less than 0.75 wt.% of calcium carbonate, based on the total weight of the film. In certain preferred embodiments, the film does not comprise a filler. In certain preferred embodiments, the film does not comprise calcium carbonate. Addition of large amounts of filler, typically greater than 1 wt.% of a filler, based on the total weight of the polymer blend, results in poor calenderability and poor print performance.

[0055] In some embodiments of the present invention, the film comprises less than 0.075 wt% of an organic acid metal salt, based on the total weight of the film. In certain embodiments, the organic acid metal salt is a salt selected from the group consisting of barium stearate, zinc stearate, and combinations thereof. In certain other embodiments, the film comprises less than 0.75 wt% of calcium carbonate, based on the total weight of the film; and less than 0.075 wt% of an organic acid metal salt, based on the total weight of the film. In certain embodiments, the film does not comprise an organic acid metal salt.

[0056] By adjusting the hardness of the polymer blend of TPU, flexible acrylic resin, and high molecular weight organic lubricant, the best balance of processability, especially calendering at room temperature and compatibility of the film is achieved. The combination of soft TPU and soft acrylic will result in a film that may be compatible, but it may not be processable and may be sticky, which leads to blocking. The combination of hard TPU and hard acrylic will lead to a film that may be processable but is brittle and not compatible at room temperature. The selection of either soft TPU and hard acrylic, or hard TPU and soft acrylic, will result in a mixture that is processable and compatible at room temperature. The addition of high molecular weight organic lubricant further improves the processability and printing performance of the film. Without being bound by theory, the specific polymer blend of the present invention provides a conformable, calenderable and printable film.

[0057] In certain embodiments, the film is calendered with or without a casting sheet or interleaf sheet as described in U.S. Pat. No. 6,520,235, the entire contents of which are incorporated herein by reference. In certain embodiments, the film is extruded with or without a casting sheet or interleaf sheet.

[0058] In some embodiments, the present invention is directed to an article comprising a film as described herein. The film can be a single layer or two or more layers. The film has a first side and a second side. An adhesive layer is applied to at least a portion of the first side of the film. The adhesive layer can be applied to the first side of the film by any suitable means. In some embodiments, the adhesive layer is a pressure sensitive adhesive layer. Optionally, printed indicia is applied to at least a portion of the second side of the film. As previously described, the printed indicia can be applied to the film by any suitable means.

[0059] FIG. 1 shows an article as described herein. Article 100 includes a film of the invention as described herein (not shown to scale), as facestock layer 10, a pressure-sensitive adhesive layer 20, and an optional release layer 30. Facestock layer 10 defines a first side 12 and an opposing second side 14. The facestock layer is shown as a single layer, but could be multiple layers. Pressure-sensitive adhesive layer 20 is applied over at least a portion of second side 14. The pressure-sensitive adhesive layer is shown as a single layer, but could be multiple layers.

[0060] The present invention is further defined in the following examples, in which all parts and percentages are by weight unless otherwise specified. It should be understood that these examples, while showing certain embodiments of the present invention, are presented for illustrative purposes only. It will be further understood that the embodiments of the present invention can be combined. From the above references and these examples, those skilled in the art can grasp the essential features of the present invention, and can make various changes and modifications to adapt the present invention to various applications and conditions without departing from the spirit and scope thereof.

[0061] Working Example The following test methods were used to evaluate the exemplary embodiments and comparative materials, unless otherwise stated.

[0062] Metal peeling To measure metal release, the material is melted between a two roll mill set up as follows: Cylinder 1 is set at a speed of 50 rpm and a temperature of 165°C. Cylinder 2 is set at a speed of 40 rpm and a temperature of 163°C. A gap set to 100 mμ is considered a gap of 0.

[0063] After complete melting of the material, the gap is set to the minimum value that allows for a film of about 50 μm, depending on the rheology of the material. The sampling speed is reduced to 20 rpm per cylinder to allow for manual peeling (or detachment). Manual peeling is performed by: Ease of peeling (manual force required for peeling); and Location of peel line It is subjectively judged based on

[0064] Chroma Area This test is used to quantify the overall color quality of the combination of printer, ink, print settings, and media using all the inks in the printer. Whereas chomaticity is usually measured for each color, the chroma area method quantifies the overall performance and simplifies the comparison of media. Film media is printed on HP Latex Gen III (Headquarters: Palo Alto, California) using the test chart shown in Figure 2 with the following profile settings: A. No ink restrictions B. No linearization C. International Color Consortium (ICC) Off

[0065] The test chart as shown in Figure 2 is acquired using Qi Image Quality (QiQ) scanning. The test chart used for testing contains various colors, but for illustration purposes, it is shown in black and white in Figure 2. Each block on the test chart represents a different color. The test chart shows how different colors, including different shades of the same color, print vividly on the film. As can be seen from the test chart, the primary printing colors of black (K), cyan (C), magenta (M), and yellow (Y) print well, as well as some combinations of each of these colors.

[0066] Chroma regions are the areas of a particular part of a swatch book, as shown in Figure 3.

[0067] [Number 2] TIFF2025506749000001.tif830

[0068] Chroma area is the area plotted on a two-dimensional chart of C values, as shown in Figure 4. For reference, PVC's score, for example, is chroma area=123.

[0069] Figure 3 shows a representative chart used in Chroma testing. The chart used for testing contains a variety of colors, but for illustration purposes it is shown in black and white in Figure 3. Each line on the chart represents a different swatch color, as follows: A14_ChromaT-Y=Yellow B14_ChromaT-R=Red C14_ChromaT-M = Magenta D14_ChromaT-B=Blue E14_ChromaT-C=Cyan F14_ChromaT-G=Green G14_ChromaT-W=White H14_ChromaT-K=Black.

[0070] Each printer contains ink of the colors black (K), cyan (C), magenta (M) and yellow (Y). Therefore, the content of each color element in the swatch chart (KCMY) is shown in the columns on the right side of the chart.

[0071] Figure 4 shows a representative two-dimensional chart of C values ​​(area) used in the chroma tests in the Examples. The two-dimensional chart includes a variety of colors, but for purposes of illustration, is shown in black and white in Figure 4. Each pattern on the chart represents a different color (or combination of colors) as shown in the table of contents of Figure 3 and described herein above.

[0072] T-Peel T-peel is used as a measure of the tendency of a film or film structure (or construction) to roll block, which is a defect in a film or film structure that occurs when adjacent films or film structures fuse or adhere together and can be observed when the film or film structure is unwound from the roll. For the examples, T-peel is measured by the Federation Internationale des fabricants et transformateurs d'Adhesifs et Thermocollants sur papiers et autres supports (FINAT) standard test FTM-1 (2019). A sample is made on a two-roll mill similar to the metal peel test, and then folded over itself with a siliconized PET stripe on the shiny side. The sample is placed in a Labtech press (manufactured by Labtech Engineering Company Ltd, headquartered in Thailand) at 40°C and 1 MPa pressure for 100 hours to simulate layer-on-layer pressure in roll form. The sample is then cooled at 20°C for a minimum of 2 hours before being removed from the press. The prepared samples are conditioned for 4 hours at room temperature and 50% relative humidity. The peel force is measured on a tensile tester according to FINAT standard test FTM-1 (2019). Data in the examples is reported as the average force of three repeats and is expressed in N / inch.

[0073] The test results are shown in the table below: · Processability is assessed using metal peeling and rated as 3=good / acceptable, 2=ok / acceptable, 1=poor / unacceptable. · Printability is assessed using chroma range and rated as >199=good / acceptable, 99-199=OK / acceptable, <99=poor / unacceptable. · Blocking is rated using the T-peel test (units: N / inch) and rated as follows: ≦1.25=acceptable, >1.25=unacceptable.

[0074] For the examples given, the flexible acrylic and TPU are listed as weight percent of the total weight of the polymer blend. The other components are listed as parts per 100 parts of the polymer blend. All examples of the present invention formed conformable films.

[0075] [Table 1]

[0076] Examples 2C-7C show that blends of acrylic core-shell polymer and TPU cannot be calendered without high molecular weight organic lubricants. Additionally, Example 8C is an example outside the required polymer blend and shows poor calenderability. Examples 9-12 are examples within the required polymer blend and show examples that are calenderable and printable using the required organic lubricants. Example 1C showed comparative calenderability and printability, but failed in tear resistance and weatherability.

[0077] [Table 2]

[0078] Examples 13-23 show the results of block copolymers as FAR within the required level in polymer blends. Polymer blends with block acrylic copolymers show good calenderability and blocking properties. Acrylic block polymers have similar biphasic chemical properties as core-shell acrylic resins, and therefore perform similarly.

[0079] [Table 3]

[0080] Examples 24-28 show the impact of increased levels of lubricant (4 phr vs. 2 phr in Examples 24-28) on calendaring, but not at the expense of printing and blocking.

[0081] [Table 4]

[0082] Examples 29-36 show that other organic lubricants can function beyond the oleic acid high Mw polyester of glycerin for calendaring and still not interfere with printability, although blocking may become an issue and require an interleaf sheet.

[0083] [Table 5]

[0084] Examples 37C-44C show that inorganic lubricants cause printability problems and some blocking problems.

[0085] [Table 6]

[0086] Examples 45-51 demonstrate dye formulations for films with the required organic lubricant in the polymer blend and the required FAR and TPU levels.

[0087] [Table 7]

[0088] Examples 52C-55C are comparative examples showing how calcium carbonate alone blocks, and the combination of lubricant and calcium carbonate shows no printability for all acrylics and no calenderability in blends. Examples 56 and 58 are examples of the invention. Examples 59-61 show a ladder of lubricant levels where metal release is improved but not at the expense of printability and T-peel.

[0089] When ranges are used herein for physical properties, such as molecular weight, or chemical properties, such as chemical formula, all combinations and sub-combinations of the ranges are intended to be included.

[0090] The disclosures of each patent, patent application and publication cited or described in this document are hereby incorporated by reference in their entirety.

[0091] It will be understood by those skilled in the art that numerous changes and modifications can be made to the embodiments of the present invention without departing from the spirit of the present invention, and it is therefore intended that the appended claims cover (or extend) equivalent modifications that fall within the true spirit and scope of the present invention.

Claims

1. 1. A film comprising a polymer blend, The polymer blend comprises: 50% to 100% by weight of a flexible acrylic resin, based on the total weight of the polymer blend; 0% to 50% by weight of a thermoplastic urethane elastomer, based on the total weight of the polymer blend; 0.1% to 10% by weight of a high molecular weight organic lubricant, based on the total weight of the polymer blend; and Including an optional dye, The film, wherein the film is processable and printable.

2. The film of claim 1 , wherein the flexible acrylic resin is at least one of a block copolymer and a multi-stage polymer.

3. The flexible acrylic resin comprises: butyl acrylate, 2-ethylhexyl acrylate, and combinations thereof. g a core layer comprising a crosslinking residue of a monomer; an optional intermediate layer; and A shell layer comprising a methacrylate polymer having a glass transition temperature greater than 100° C.

3. The film of claim 1 or 2, which is a multistage acrylic polymer comprising:

4. 10. The film of claim 1, wherein the flexible acrylic resin is present in an amount ranging from 50% to 95% by weight, based on the total weight of the polymer blend.

5. The film of claim 1 , wherein the flexible acrylic has a Shore D hardness of about 40 to about 60.

6. 10. The film of claim 1, wherein the thermoplastic urethane elastomer is selected from the group consisting of polyether-based polyurethanes, polyester-based polyurethanes, polycarbonate-based polyurethanes, and combinations thereof.

7. The film of claim 1, wherein the thermoplastic urethane elastomer is present in an amount ranging from 5% to 50% by weight, based on the total weight of the polymer blend.

8. The film of claim 1 , wherein the thermoplastic urethane elastomer has a Shore D hardness of about 55 to about 95.

9. 10. The film of claim 1, wherein the thermoplastic urethane elastomer has a Shore D hardness of at least 65.

10. 2. The film of claim 1, wherein the high molecular weight organic lubricant is a high molecular weight polyester lubricant.

11. 11. The film of claim 10, wherein the polymeric polyester is the reaction product of a fatty acid selected from the group consisting of oleic acid, stearic acid, hydroxystearic acid, and combinations thereof, and an alcohol selected from the group consisting of butanol, octanol, glycerol, pentaerythritol, and combinations thereof.

12. 10. The film of claim 1, wherein the high molecular weight organic lubricant is present in an amount ranging from 1% to 5% by weight, based on the total weight of the polymer blend.

13. The film of claim 1 , wherein the high molecular weight organic lubricant has a molecular weight of at least about 1,500 Da.

14. The film of claim 13, wherein the high molecular weight organic lubricant has a molecular weight of at least about 1,500 Da to about 50,000 Da.

15. The film of claim 1 , wherein the pigment is present and the pigment is titanium dioxide.

16. 10. The film of claim 1, wherein the polymer blend further comprises up to 1 weight percent of a filler, based on the total weight of the polymer blend.

17. 10. The film of claim 1, wherein the polymer blend comprises less than 0.75 weight percent of a filler, based on the total weight of the polymer blend; and the filler is calcium carbonate.

18. 10. The film of claim 1, wherein the polymer blend comprises less than 0.075 wt. % of an organic acid metal salt, based on the total weight of the polymer blend.

19. 20. The film of claim 18, wherein the organic acid metal salt is a salt selected from the group consisting of barium stearate, zinc stearate, and combinations thereof.

20. The film of claim 1 , wherein the polymer blend is free of calcium carbonate.

21. The film of claim 1 , wherein the polymer blend is free of organic acid metal salts.

22. The film of claim 1 , wherein the polymer blend does not include hydrogen bonding monomers.

23. The film of claim 1, wherein the film has a thickness of from 30 μm to 200 μm.

24. 10. The film of claim 1, wherein the film is calendered.

25. An article comprising the film of any one of claims 1 to 24, the film having a first side and a second side; applying an adhesive layer to at least a portion of the first surface of the film; an optional printed indicia applied to at least a portion of the second surface of said film; and The article, wherein an optional release layer is applied over the adhesive layer.

Citation Information

Patent Citations

  • Resin composition for acrylic cap stock

    JP2003128869A

  • Soft resin composition and composite-molded product

    JP2004238590A

  • Laminated sheet for designed coating and metal sheet coated with laminated sheet

    JP2007045067A

  • Light-emitting device

    JP2018060841A

  • Acrylic resin composition for calender molding and film formed of the resin composition

    JP2020117676A